Analysis of Social Determinants and Health Service Access on the Occurrence of Unintended Pregnancy among Adolescent Girls in Urban Indonesia - Fatimah (PT Inovasi Pratama Internasional, 2026)
Unintended pregnancy among adolescent girls in urban Indonesia remains a critical public health and social concern, with important implications for maternal and neonatal outcomes, education, and intergenerational poverty. Quantitative analyses based on the Indonesia Demographic and Health Survey (IDHS) and recent national studies indicate that residence, age, education, employment, wealth, parity, and prior contraceptive use are associated with unintended pregnancy, and that risk is particularly elevated among women aged 15–19 years and those living in urban areas. Concurrently, utilization of adolescent reproductive health services in urban settings is low, and adolescents have limited knowledge and access to reliable sexual and reproductive health (SRH) information. This study presents a quantitative integrative analysis of national survey data and peer‑reviewed quantitative studies to examine how social determinants and access to SRH services shape unintended pregnancy among adolescent girls in urban Indonesia. Data were extracted from IDHS 2017 and other large‑scale surveys, complemented by urban‑focused studies on adolescent SRH service utilization. Key findings show that younger age, urban residence, low education, poverty, and limited contraceptive knowledge or inconsistent use interact with weak access to youth‑friendly services to increase the likelihood of unintended pregnancy. Strengthening comprehensive sexuality education, youth‑friendly service provision, and multi‑sectoral social protection in urban areas is essential to reduce unintended pregnancy among Indonesian adolescent girls